Not in Employment, Education or Training (NEET) Among the Youth in Indonesia: The Effects of Social Activities, Access to Information, and Language Skills on NEET Youth - Pattinasarany, Indera Ratna Irawati (UI Scholars Hub, 2019)
This article attempts to describe the prevalence of NEET (Not in Employment, Education or Training) among youth aged 15-24 in Indonesia, who in general live in a high risk and vulnerable condition, many of whom are facing social injustice. Previous analyses on NEET in Indonesia utilized labor force surveys; this study emphasizes on employment and education backgrounds of individuals. This article constructs NEET from the household surveys SUSENAS (National Socio-Economic Survey) and related MSBP (Module of Social, Cultural, and Education) of 2015. The richness of information collected in these surveys enables the author to analyze factors affecting Indonesian youth to be NEET beyond those related to employment matters. By using a logistic regression analysis, this article explains reasons for youth becoming NEET based on their engagement in social activities, access to information, and capability to read and write in Latin, Arabic, or other alphabets. This article finds that the youth who attend local meetings, actively engage in religious activities and/or community and social services, access the internet, and can read and write Latin and other non-Arabic alphabets have a lower likelihood to become NEET.